Level of speed abilities of young football players in various training periods - P. Kalinowski; D. Jerszyński; M. Nowakowska (H.S. Skovoroda Kharkiv National Pedagogical University, 2021)
Purpose: At the highest level of the competition, the players tend to have a comprehensive motor, technical-tactical and mental preparation. It is assumed that in the training process of young players, speed is an important factor determining sports success. Therefore, the aim of the study was to try to compare the speed abilities indicator of young footballers during the summer and winter preparatory period. Material and methods: The research was conducted in July 2019 and January 2020 in Poznań. The research subject consisted of 23 young players of the Warta Poznań club in the age category of the junior football players (U14). Results: The results were statistically processed, basic descriptive characteristics were made, the normality of the distribution of differences was checked using the Shapiro-Wilk test, and the collected results from two tests dates were compared using the Student's t-test for dependent samples. Based on the the conducted research, no significant change in the starting speed level was observed at the distance of 5 meters and 15 meters, while an improvement in the level of speed abilities in terms of locomotion at the distance of 30 meters was noted. Conclusions. The level of running speed at a distance of 30 meters in the tested competitors changed in the six-month preparation cycle. There was no change in the starting speed level over the distance of 5 and 15 meters in the competition season between the preparatory period and the end of the autumn round in the competitors of the Poznań Warta club. On the basis of the conducted research, it is worth conducting experimental research based on individualized speed training on a group of 13 - 14 year old players.